2016
DOI: 10.1055/s-0035-1561860
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a New Polyfunctionalised Pyrimidine-4-carboxylate and Its Application for the Construction of a Series of Pyrimidine Derivatives

Abstract: The synthesis of a new and versatile polyfunctionalised pyrimidine-4-carboxylate, along with the study of its reactivity against 1,2-dinucleophiles and 1,4-dinucleophiles, is reported. These simple and efficient methodologies allowed for the synthesis of novel pyrimidine derivatives such as pyrimido[4,5-d]pyridazin-8-one-5-carboxylates and their corresponding carbohydrazides and N-acylhydrazone (NAH) derivatives, pyrimido[4,5-d][1,2]oxazin-8-one and its corresponding carbohydrazide derivative, and 3-pyrimidiny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…These results are consistent with oxazinone yields lower than 70% reported in previous studies and the tendency for yields to be lower when halogen is the substituent. 18,32,57,58 Only Gonçalves et al (2016) and Shamala, D. and Shivashankar, K. (2017) reported yields greater than 90%, achieved using pyridine and DBU as catalysts under basic reaction conditions. 58,59…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are consistent with oxazinone yields lower than 70% reported in previous studies and the tendency for yields to be lower when halogen is the substituent. 18,32,57,58 Only Gonçalves et al (2016) and Shamala, D. and Shivashankar, K. (2017) reported yields greater than 90%, achieved using pyridine and DBU as catalysts under basic reaction conditions. 58,59…”
Section: Resultsmentioning
confidence: 99%
“… 18,32,57,58 Only Gonçalves et al (2016) and Shamala, D. and Shivashankar, K. (2017) reported yields greater than 90%, achieved using pyridine and DBU as catalysts under basic reaction conditions. 58,59 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…a Yield is given for both regioisomers b Reverse regioselectivity has been also reported[132,133].Scheme 23. 2-(1H-Pyrazol-1-yl)pyrimidine-4-carboxylates 58.…”
mentioning
confidence: 79%
“…Enaminone 51 bearing an additional ester group also proved to be a good reagent for the preparation of pyrimidines (Scheme 21); representative examples included acetal 52 [128][129][130] The scope of reported enones included derivative 54 [132,133] decorated with two glyoxylate moieties (Scheme 22) and other polycarbonyl enones 55. An interesting study revealed that their condensation with NCN binucleophiles, e.g.…”
Section: β-Alkoxyvinyl-and β-Enamino α-Ketoestersmentioning
confidence: 99%